2017
DOI: 10.7759/cureus.1337
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Breast Cancer with BRCA Mutation Discovered By Next-Generation Sequencing Responding to Olaparib

Abstract: Breast cancer susceptibility genes 1 and 2 (BRCA1 and BRCA2) mutations are associated with hereditary breast and ovarian cancer syndromes (HBOC). However, certain individuals with breast cancer do not meet high-risk factors for hereditary breast cancer screening based on age, family history, and biology of malignancy.We present a patient with relapsed breast cancer who developed progressive disease with significant tumor burden causing a recurrent pleural effusion. Next-generation sequencing (NGS) done on a tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Breast cancers have low expression of MHC I antigens and relatively low state of immunogenicity to escape from immune recognition. 16 18 However, breast cancers with high TMB value were indicative of potentially more neoantigens and elicited an appropriate adaptive immune response with immunotherapy. In support of this, a retrospective study using TMB as a marker in the Phase III clinical trial of CheckMate 026 showed that TMB was superior to PD-L1 expression as a biomarker to distinguish those who would benefit from Opdivo in non-small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancers have low expression of MHC I antigens and relatively low state of immunogenicity to escape from immune recognition. 16 18 However, breast cancers with high TMB value were indicative of potentially more neoantigens and elicited an appropriate adaptive immune response with immunotherapy. In support of this, a retrospective study using TMB as a marker in the Phase III clinical trial of CheckMate 026 showed that TMB was superior to PD-L1 expression as a biomarker to distinguish those who would benefit from Opdivo in non-small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 1 According to the American Cancer Society, an estimated 252 710 new cases of invasive BC will be diagnosed and 40 610 cancer deaths will be occurred in BC in 2017. 2 The main carcinogenic factors, including genetic mutations, endocrine disorders, and decline in immune function may increase the risk of developing BC. 3 Chemotherapy is one of the current main anticancer therapies for the treatment of BC which has shown to inhibit tumor growth and prolong patient survival.…”
mentioning
confidence: 99%
“…Patients with ovarian cancer who carry BRCA1/2 mutations are very sensitive to platinum‐based chemotherapy with good prognosis (Byrski et al, ), and can benefit from treatment with poly ADP‐ribosome polymerase inhibitors (Isakoff, ; Rouleau, Patel, Hendzel, Kaufmann, & Poirier, ; Ström et al, ). Clinical studies have shown that prophylactic bilateral mammectomy or bilateral oophorectomy can reduce 50%–90% of the risk of breast and ovarian cancer in women who have family history of breast cancer and carry BRCA1/2 mutations (Domchek & Kaunitz, ; Rizvi, Truong, & Truong, ). With the advancement of precision medicine and targeted therapy, detection of BRCA1/2 mutations in blood and/or tumor tissues of patients with breast and ovarian cancer will help select targeted drugs and chemotherapy regimens and better assess prognosis (Robson et al, ).…”
Section: Discussionmentioning
confidence: 99%